Sonophotochemical and photochemical efffiiciency of thiazole- containing metal phthalocyanines and their gold nanoconjugates - Farajzadeh, Nazli; Yenilmez, Hacer Yasemin; Atmaca, Goknur Yasa; Erdogmus, Ali; Bayir, Zehra Altuntas (Tubitak Scientific & Technological Research Council Turkey, 2023)
This study presents the synthesis of some metal {M = Zn(II), Lu(III), Si(IV)} phthalocyanines bearing chlorine and 2-(4-methylthiazol-5-yl) ethoxy groups at peripheral or axial positions. The newly synthesized metal phthalocyanines were characterized by applying FT-IR,1H NMR, mass, and UV-Vis spectroscopic approaches. Additionally, the surface of gold nanoparticles was modified with zinc(II) and silicon(IV) phthalocyanines. The resultant nanoconjugates were characterized using TEM images. Moreover, the effect of metal ions and position of substituent, and gold nanoparticles on the photochemical and sonophotochemical properties of the studied phthalocyanines was investigated. The highest singlet oxygen quantum yield was obtained for the lutetium phthalocyanine by applying photochemical and sonophotochemical methods. However, the linkage of the zinc(II) and silicon(IV) phthalocyanines to the surface of gold nanoparticles improved significantly their singlet oxygen generation capacities.
Keywords: Phthalocyanines; gold nanoparticles; nanoconjugate; sonophotochemical; photochemical; SYMMETRY ZINC PHTHALOCYANINE; PHOTODYNAMIC THERAPY; SUBSTITUTED METALLOPHTHALOCYANINES; IN-VITRO; NANOPARTICLES; FLUORESCENCE; CANCER; INCREASE; PROGRESS; LIGANDS; Chemistry; Engineering